RANCANG BANGUN APLIKASI FASE KEHAMILAN BERBASIS ANDROID MENGGUNAKAN METODE FUZZY LOGIC PADA PUSKESMAS CARENANG - Sandi Yogo Dwi; Raden Kania; Tauffik Qurohman (LPPM Unbaja, 2021)
Pregnancy is a major global concern in today's health issues. The maternal mortality rate (MMR), which is still quite large in almost all countries in the world, is a separate concern that makes all countries try to reduce their percentage every year. In general, maternal mortality is caused by factors: the lack of knowledge of pregnant women about handling and what to do during pregnancy, improper handling also results in contraction of pregnant women and other pregnancy symptoms. The purpose of this study is to design and build an information system that can be used by pregnant women, using research methods of data collection by study library, interview, and observation, and using the watervall system design method to analyze the existing system and build a new system. In modeling this application using the UML method in the form of use case diagrams, class diagrams, activity diagrams, and sequence diagrams. The results of this study are the production of an Android based pregnancy phase application for pregnant women named Pregnancy phase applications